Board diversity and audit quality among selected listed food and beverage firms on the Nigeria Exchange Group - Segun Idowu Adeniyi; Vincent Ayeole Aderobaki (UNIVERSITAS PEMBANGUNAN NASIONAL VETERAN JAWA TIMUR, 2022)
This study is to ascertain the effect of ethnicity diversity, skill, expertise and experience diversity and interaction of ethnicity diversity and skill, expertise and experience diversity on audit quality of listed brewery firms in Nigeria. The study used Ex-Post Facto research design. The Population of the study consists of five (5) brewery firms listed on the Nigerian Stock Exchange (NSE) as at December, 2019. Purposive sampling technique was adopted in selecting the three (3) listed food and beverage firms which form the unit of analysis for this study. The panel data were derived from annual reports and accounts with Nigeria Stock Exchange Fact book for the period of ten years spanning from 2010 to 2019. The Ordinary Least Square (OLS) statistical technique was adopted in the analysis of data. The statistical procedures were programmed using SPSS 20.0 software. The study discovered that ethnicity diversity, and skill, expertise and experience diversity does not significantly affect audit quality while the interaction of ethnicity diversity and skill, expertise and experience diversity affects audit quality. Therefore the study recommends among others that ethnicity diversity need not to be considered in corporate board composition and it should not be made compulsory for board members to have certificate in Accounting, have experience in financial reporting or auditing.